2020
DOI: 10.1002/cssc.202001225
|View full text |Cite
|
Sign up to set email alerts
|

Lignin Depolymerization under Continuous‐Flow Conditions: Highlights of Recent Developments

Abstract: Lignin is a polyaromatic polymer contained in plant cell walls, and it is considered the most abundant noncarbohydrate polymer on Earth. The aromaticity and richness of its functional groups render lignin an attractive starting biomacromolecule for conversion into a variety of value‐added products. The development of successful strategies for lignin valorization infers the design of effective depolymerization protocols. Most research on lignin depolymerization has focused on batch‐mode processing, whereas only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…For example, controlled lignin depolymerization under continuous flow conditions has been demonstrated. [53] By controlling the flow reactor parameters (flow rate, pressure, temperature, and column design), it is possible to obtain optimized depolymerization and autonomic degradation reactions in the next generation of self-immolative polymers. [54] Optimizing fluid properties such as viscosity and overcoming thermal conductivity-driven limitations should be a primary focus while studying kinetics of depolymerization and the amplification of reaction rates.…”
Section: Prospective Direction: Depolymerization In the Presence Of Fluid Flowmentioning
confidence: 99%
“…For example, controlled lignin depolymerization under continuous flow conditions has been demonstrated. [53] By controlling the flow reactor parameters (flow rate, pressure, temperature, and column design), it is possible to obtain optimized depolymerization and autonomic degradation reactions in the next generation of self-immolative polymers. [54] Optimizing fluid properties such as viscosity and overcoming thermal conductivity-driven limitations should be a primary focus while studying kinetics of depolymerization and the amplification of reaction rates.…”
Section: Prospective Direction: Depolymerization In the Presence Of Fluid Flowmentioning
confidence: 99%
“…Lignin is the most abundant naturally occurring aromatic polymer on Earth and has excellent potential as a renewable feedstock for the production of chemicals, fuels, and functional materials. Lignin is also a major side‐product from the pulp and paper industry and cellulosic ethanol production, presenting a bulk raw material commonly referred to as technical lignin [1] . Despite its immense potential, lignin is still vastly underutilized and is primarily burned for energy recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning lignin, it has now been demonstrated that the main constituents are p-coumaryl, coniferyl and sinapyl alcohols featuring phenol, alkenes and allylic alcohol scaffolds. The lignin depolymerization method, both under batch or continuous flow conditions [9], as well as lignin's origin (hardwood, softwood or herbaceous crops) affects the proportion of these three constituents and their derivatives, opening the doors to a variety of transformations [10,11]. Among those transformations, Antoniotti and coworkers reported in 2007 both batch and continuous flow conditions procedures allowing the selective oxidation of a broad scope of alcohols, among which coniferyl alcohol derivatives, into the corresponding aldehydes or ketones through aerobic oxidation catalyzed by heterogenous gold nanoparticles [12].…”
Section: Introductionmentioning
confidence: 99%